The dilemma of the translation concept in Islamic sources - Yaacob, Solehah@Nik Najah Fadilah (Global Journals, 2019)
Epistemology is a theory of knowledge especially with regards to its methods, validity and scope; it is an investigation of what distinguishes that which has to be justified as belief or opinion. In explaining the monotheistic law, the religious perspective, looks at the Quranic epistemology as a theory of knowledge which is absolutely primordial and ineluctable precept of the oneness of God as the priori premise of knowledge. In explaining knowledge formation based on emergent events the contemporary Islamic scholars have failed to incorporate substantively the Quranic methodological worldview in the form of epistemological analytics and its function. How to understand Quranic epistemology? The prerequisite is an understanding of the Arabic language including syntax, morphology, rhetoric and the ability to recite the Quran properly. Without these, Islamization of knowledge would be regarded as academic rhetoric. This research critically discusses issues on some blockages facing the Islamization agenda.